(untitled) (Voice of Teacher, 2021)
This Paper is based on the study of girl students studying at Bachelor level in mathematics in six reputed educational institutes situated in Kathmandu Valley. The Paper is guided by three objectives – to examine the historical trend of girl students offering mathematics at the Bachelor level, to examine the possibility of increasing the enrollment of these students, and to identify policy instruments that can help increase their participation. Low number of girl students, low number of female teachers, limited availability of resources and equipment are among the important features that characterize the Bachelor level education in Mathematics. The Paper also enumerates some policy instruments that can assure the future career prospects of girl students studying mathematics.